The Lure of Hope : On the Transnational Surrogacy Trail from Australia to India. - Stockey-Bridge, Michaela (Blue Ridge Summit : Fairleigh Dickinson University Press, 2017)
India was the first among a trail of "pop up" third-party reproductive destinations including Thailand, Nepal, Mexico, and now Cambodia. Alongside the detailed ethnographic account of the experiences of parents and surrogate mothers the author offers a careful analysis of regulatory systems governing surrogacy and embryo use in Australia and India.
Intro -- Contents -- Preface -- Acknowledgments -- Introduction -- 1 Genealogies of Transnational Commercial Surrogacy -- 2 Surrogates in India -- 3 The Intending Parents -- 4 Finding the Clinic -- 5 Caretakers and Conversion -- 6 The Lure of Hope -- 7 The Rhetoric of Tragedy and the Experience of Disaster -- 8 Transnational Surrogacy, Kinship, Connectedness, and the Gift -- Conclusion -- Terminology -- Appendix -- References -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Surrogate motherhood-Economic aspects; Human reproductive technology-Social aspects; Electronic books